Changes in lip, cheek, and tongue pressures after rapid maxillary expansion using a diaphragm pressure transducer - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2003)
The purpose of this study was to investigate the changes in pressures that are exerted to maxilla by the tongue, lip, and cheek before and after expansion and during the retention period. Twelve patients (five males, seven females) with maxillary transverse deficiencies were randomly selected. The first pressure measurements were made before expansion using a diaphragm pressure transducer. The second measurements were made right after the maxillary expansion procedure, which lasted about 20 days. The expansion devices were replaced with retention devices, and measurements were made at the end of the first, second, and third months of retention. Pressure values on the buccal side of upper first molar and incisor increased significantly right after expansion but started decreasing during retention. The values at the end of the third month of retention were similar to the preexpansion values (P < .05). Tongue pressures on the lingual side of the upper first molar and upper incisor decreased significantly with expansion but started increasing after the expansion procedure. Even at the end of the third month of the retention period, the values were not similar to the preexpansion values (P < .05). These values show that the cheeks and lips almost adapt to the new position of dental arches at the end of the third month, whereas tongue adaptation took comparatively longer.
Keywords: transducer; pressure; RME; PALATAL EXPANSION